Praktyczne aspekty efektywnego nadzoru nad transgraniczną działalnością banków nieposiadających siedziby w Unii Europejskiej na tle prawa polskiego - Duraj, Marta (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article is aimed at presenting the potential problems arising out of the cross-border banking activities undertaken by the banks registered outside the EU. The effectiveness of the financial supervision is strongly connected with the fact that the Polish financial supervision authority Komisja Nadzoru Finansowego — KNF disposes over relevant means to control the banks and to execute restrictions imposed over the banks.Rendering the cross-border banking services is regulated by the EU law, which allows the banks incorporated in one EU member state to render banking services in other EU countries without obtaining a relevant permit there so-called EU pass. On the other hand, according to Polish regulations, rendering cross-border banking services from outside the European Union, without physical presence in Poland and obtaining a permit from KNF, is not admissible. Consequently, in order to undertake banking business activity in Poland, it would be inevitable to establish a branch or a subsidiary company there and in order to advertise and promote the foreign bank — a representative office.However, there are several activities, which do not fall within the scope of either rendering banking activities in Poland or advertising and promoting the foreign bank, namely: activities which could be classified as a part of the relationship with the existing clients under the agreement concluded in the state of incorporation of the bank, under foreign law, sending information about the foreign bank on the potential client’s initiative and having website accessible from Poland.Although there is no clear legal basis for clear classification of the above-mentioned issues, the Author represents the opinion that:• having a website accessible from Poland which does not include any offer directed to the Polish customers,• or undertaking activities towards existing clients domiciled in Poland under the agreement concluded under foreign law in the state of incorporation of the bank, which do not include rendering banking services in Poland,• or sending information about the bank on potential client’s initiativedo not require obtaining a relevant permit from KNF and, consequently, do not require establishing a branch, subsidiary or representative office in Poland.It should be noted, though, that the foreign banks undertaking the cross-border activities in Poland are subject to the foreign financial supervision system. Therefore, the effectiveness of the supervision might be threatened, especially in case when the foreign bank decides to render any banking activities in Poland or to promote itself there. The latter would lead to violation of Polish law, but the possibility of executing any restrictions against the bank might seem to be difficult.According to the above-mentioned problems, it seems necessary that the Polish financial supervision authority issues an official interpretation of the potential cross-border activities which may and may not be undertaken towards Polish clients without obtaining the relevant permit and physical presence in Poland.
Keywords: prawo polskie; banki; transgraniczna działalność banków; nadzór; praktyczne aspekty